Estrogen prevents bovine aortic endothelial cells from TNF-alpha-induced apoptosis via opposing effects on p38 and p44/42 CCDPK. - LIU Wen-Lan; GUO Xun; GUO Zhao-Gui (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the effect of 17beta-estradiol (E2) on TNF-alpha-induced apoptosis in cultured bovine aortic endothelial cells (BAEC) and the underlied mechanism. METHODS: BAEC were cultured and passaged in Dulbecco's modified Eagle's medium (DMEM). Morphologic changes and quantification of apoptotic cells were determined under fluorescence microscope with Hoechst 33258 staining. Cell viability was detected with MTT method. DNA fragmentation was visualized by agarose gel electrophoresis. The expression of phospho-p38 and phospho-p44/42 Ca2+-calmodulin dependent protein kinase (CCDPK) was measured by Western blotting. RESULTS: TNF-alpha 5000 kU/L elicited typical apoptotic morphologic changes (chromatic condensation, nucleus fragmentation, and DNA fragmentation). E2 0.1 pmol/L-100 nmol/L enhanced the expression of phospho-p44/42 CCDPK induced by TNF-alpha, at the same time, inhibited TNF-alpha induced activation of p38 CCDPK. E2 protected BAEC from apoptosis induced by TNF-alpha in a concentration-dependent manner. DNA fragmentation induced by TNF-alpha 5000 kU/L was also reduced by E2 1 nmol/L. Both the E2-induced upregulation of phospho-p44/42 CCDPK and its anti-apoptotic action were prevented by the specific p44/42 CCDPK inhibitor U0126. CONCLUSION: Activation of p44/42 CCDPK signaling together with inhibition of p38 CCDPK signaling by E2 appears to be an important mechanism for its survival effect on endothelial cells.